Self-Assembled Monolayers on C(0001) - Terán Arce, Fernando (2008)
This chapter describes the application of tunneling and AFM to the study of inorganic and organic adsorbates on C(0001) at the submonolayer and ML level. The C(0001) surface can be taken as a model system for the study of adsorption processes because it is atomically smooth and exhibits a low chemical reactivity, allowing an easy handling in the atmosphere. The knowledge of adsorption on carbon is important in the field of electrocatalysis because carbon is widely used as a matrix for the dispersion of catalytically active metallic clusters.